Conceptualizing Alkali Pozzolan Cement - Kulasuriya, Chandana; Vimonsatit, Vanissorn (Khavaran Institute of Higher Education, 2012)
This paper presents an overview of past research related to the activation of pozzolanic materials and past research related to preparation of alkali pozzolan mortar and concrete by mixing pozzolanic materials and alkali liquids. This research is different from those research, as the aim of this research is not to make mortar or concrete, but to make a ‘cement’ that could be stored as a product. It investigates the feasibility of producing ‘Alkali Pozzolana Cement’ (APC) by mixing pozzolanic materials and non-hostile dry form of alkali materials and chemical activators. The main alkali material considered is a dry powder form of lime, and the pozzolanic material used is fly ash. A series of experiments has been conducted, and the initial findings indicate that APC mortar exhibits relatively low strength when compared with OPC mortar. This is due to the slow reaction between alkali and pozzolanic materials and the slow strength gain of the lime-fly ash compound. This has led to a further investigation on the possibility of adding non-hostile activating chemicals to activate the reaction between fly ash and lime and adding small quantity of OPC to enhance the initial strength. Based on the chemical composition of fly ash available in Western Australia, this study proposes the proportion of fly ash and lime to be mixed and the quantity of activating chemicals and OPC to be added. Finally the paper discusses the potential and limitations of APC mixtures and the feasibility of using APC as sustainable cement for the future.